İmar hukukunda idari yaptırımlar - Aydın, Muhammed Ali (My University, 2022)
Bu çalışmanın konusunu imar hukukuna aykırı fiiller, bu fiillere uygulanan idari yaptırımlar ve bu yaptırımların uygulandığı kişilerin başvurabileceği idari ve yargısal yollar oluşturmaktadır. Birinci bölümde idari yaptırım uygulanmasını gerektiren imar hukukuna aykırı fiiller incelenmektedir. Bu bölümde; yapılardaki idari yaptırım gerektiren uygulamaların yanı sıra müellif, fenni mesuliyet, şantiye şefliği, yapı müteahhitliği, yapı denetimi gibi mesleklerin kendi sorumluluk alanlarına ilişkin idari yaptırım gerektiren fiil ve yükümlülüklere aykırılıklar incelenmiştir. İkinci bölümde, imar hukukunda idari yaptırım türleri olarak yıkım, idari para cezaları, uyarı, yeni iş almaktan men cezası ile lisans/ izin belgesi iptali incelenmiştir. Bu yaptırım türlerinin çeşitleri, hangi hallerde kim tarafından hangi şekilde uygulandıkları ve idari para cezaları açısından cezanın miktarının belirlenmesi konuları değerlendirilmiştir. Üçüncü bölümde, idari yaptırımlara karşı idari başvuru yolları ile yargısal başvuru yolları incelenmiştir. Yargılama usulü kuralları, mahkemede ilk inceleme konusu olan hususlar ile idari yaptırımın esasına ilişkin bazı hususlar değerlendirilmiştir. Başvuru ve itiraz yollarına ilişkin olarak ise görevli ve yetkili mahkemeler, dava açma süreleri, yürütmeyi durdurma, bilirkişi görevlendirilmesi gibi haller ile mahkeme kararlarının hangi aşamada kesinleşeceği gibi hususlara yer verilmiştir.

The subjects of this study are acts against the zoning law, administrative sanctions imposed on these acts and administrative and judicial remedies that can be claimed by those who are subjected to these sanctions. In the first chapter, acts against to zoning law, which require administrative sanctions, have been examined. In this chapter; illegal revisions related to constractions have been examined. In addition, cases of breach of obligations related to the responsibilities of professional groups such as project owner, engineer of record, construction supervisor, construction contractor, construction inspector have been examined. In the second chapter, types of administrative sanctions in zoning law such as demolition and administrative fines have been examined. In this section, the following issues have been examined: (i) the types of above-mentioned sanctions, (ii) the cases in which these sanctions are applied, (iii) the persons/ institutions applying these sanctions, (iv) the procedure for applying these sanctions, (v) determination of the amount of the penalty in case of administrative fines.. In the third chapter, administrative remedies and judicial remedies against administrative sanctions have been examined. The rules of judicial procedure, the issues that were the subject of the first examination in the court and the essence of the administrative sanction have been evaluated. Administrative sanctions have been evaluated in terms of authority, form, reason, subject and purpose, which are the elements of the administrative act. As for application and objection methods, issues such as competent and authorized courts, time to file a lawsuit, suspension of execution, appointment of experts and at what stage the court decisions will be finalized have been included.
Keywords: administrative fines related to zoning law; idari para cezası; idari yaptırım türleri; İmar hukuku; imar hukukuna aykırı fiiller; imar para cezası acts against zoning law; Kamu hukuku; Public law; types of administrative sanctions; yıkım; Zoning law